The Cortical Development of Specialized Face Processing in Infancy. Issue 5 (31st May 2016) - Guy, Maggie W.; Zieber, Nicole; Richards, John E.
Abstract : The aim of this study was to examine specialized face processing in forty‐eight 4.5‐ to 7.5‐month‐old infants by recording event‐related potentials (ERPs) in response to faces and toys, and to determine the cortical sources of these signals using realistic, age‐appropriate head models. All ERP components (i.e., N290, P400, Nc) showed greater amplitude during periods of attention than inattention. Amplitude was greater to faces than toys during attention at the N290, and greater to toys at the P400. Cortical source analysis revealed activity in occipital–temporal brain areas as the source of the N290, particularly the middle fusiform gyrus. The Nc and P400 were the result of activation in midline frontal and parietal, anterior temporal, and posterior temporal and occipital brain areas.